The Capital Budgeting Decision: Economic Analysis Of Investment Project - BIERMAN, Harold ([Tidak Terdaftar], 1993)
Individuals and businesses face large numbers of decisions where it is reasonably feasible to quantify key costs and benefits of a project. This invaluable book enables the decision-maker to make sensible choices when elements of time and risk are present. While other measures can help describe the outcomes, Bierman and Smidt's book focuses on the theme of net present value (NPV), of how it is the most reliable single measure of value, and of how it is important for the users of these tools to understand their limitations. This book was a classic text and ran to eight editions as a Macmillan text before being taken on by Prentice Hall. By this time it had become unwieldy and had split into an introductory and advanced volume. As Prentice Hall released the rights in the introductory volume, the authors propose that this new book (or 9th edition tbc) should return to its roots as a clear and concise introduction to this complex but essential topic in corporate finance. A new theme of this edition is adjusting for uncertainty and a wholly new chapter exploring the use of Real Options has been added.